Chromosomal Mapping of Repetitive DNA Sequences in Five Species of Astyanax (Characiformes, Characidae) Reveals Independent Location of U1 and U2 snRNA Sites and Association of U1 snRNA and 5S rDNA - Silva, Duilio M. Z. A. [UNESP]; Utsunomia, Ricardo [UNESP]; Pansonato-Alves, Jose C. [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Karger, 2015)
Astyanax is a genus of Characidae fishes currently composed of 155 valid species. Previous cytogenetic studies revealed high chromosomal diversification among them, and several studies have been performed using traditional cytogenetic techniques to investigate karyotypes and chromosomal locations of 18S and 5S rDNA genes. However, only a few studies are currently available about other repetitive sequences. Here, the chromosomal location of small nuclear RNA genes, identified as U1 and U2 snRNA clusters, was established and compared to the distribution of 5S rDNA and histone clusters in 5 Astyanax species (A. paranae, A. fasciatus, A. bockmanni, A. altiparanae, and A. jordani) using FISH. The cytogenetic mapping of U1 and U2 snRNA demonstrated a conserved pattern in the number of sites per genome independent of the location in Astyanax species. The location of the U1 snRNA gene was frequently associated with 5S rDNA sequences, indicating a possible interaction between the distinct repetitive DNA families. Finally, comparisons involving the location of U1 and U2 snRNA clusters in the chromosomes of Astyanax species revealed a very diverse pattern, suggesting that many rearrangements have occurred during the diversification process of this group. (C) 2015 S. Karger AG, Basel
Keywords: Fish cytogenetics; Genome evolution; Histone genes; rDNA; U snRNA